STUDI KOMPARATIF MATERI BUKU AJAR PAI RISTEKDIKTI DAN PRODUK PENGEMBANGANNYA BAGI CALON PENDIDIK - Isgandi, Yiyin; Prasodjo, Pandu (Universitas Muhammadiyah Semarang, 2018)
This paper aims to describe the similarities and the differences which talkdeeply about the strengths and weaknesses of PAI Ristekdikti Textbook and its development product for pre-teacher students. This qualitative research uses documentation. The collected data is analyzed using content analysis and comparative descriptive analysis. The result shows that the similarities of those two textbooks are in the general purpose and main subject matter, the main sources, as well the suitability of the SN DIKTI, KKNI, and the goal of PAI learning. The most prominent difference is that the developed material is arranged and it has met the needs of pre-teacher students, strengthening the values of character and nationalist spirit at the end of each chapter, presenting indicators of learning objectives at the beginning of each chapter, and enriching noble moral habituation. The shortcomings are in the ‘burhani’ scientific approach and the enrichment of Islamic civilization. While the PAIRistekdikti Textbook stands out in the ‘burhani’ scientific approach that isinterconnected with Psychology, Social, Theology, and Philosophy, enriching insights into Islamic civilization, and Indonesian contextualization. The shortcomings are in the form of inconsistencies in writing sources from the verses of the Qur'an and the hadith, the lack of material that is integrated with teacher’s characters and nationalist spirit.Keywords: Comparative study, PAI textbook, development, pre-teacher student